2015
DOI: 10.1007/s11665-015-1460-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effects of Processing Parameters on Dynamic Recrystallization Behavior of Deformed 38MnVS6 Steel

Abstract: The dynamic recrystallization (DRX) and grain growth mathematical models of 38MnVS6 steel were obtained on the basis of the results from hot compression tests and isothermal annealing tests on a Gleeble-1500 thermo-mechanical simulator. A three-dimensional finite element model was established to investigate the compression process. In order to predict the evolution of DRX volume fraction and austenite grain sizes, a subprogram was designed and coupled in the FE model. The effects of deformation temperatures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…With the further increase of true strain, the true stress gradually decreases. When the dynamic balance between work hardening and flow softening is reached, the steady stress appears [37,38,39]. Meanwhile, it is also observed that the true stress decreases with the increase of deformation temperature.…”
Section: High-temperature Deformation Behaviormentioning
confidence: 98%
“…With the further increase of true strain, the true stress gradually decreases. When the dynamic balance between work hardening and flow softening is reached, the steady stress appears [37,38,39]. Meanwhile, it is also observed that the true stress decreases with the increase of deformation temperature.…”
Section: High-temperature Deformation Behaviormentioning
confidence: 98%
“…Wherein, the aim was to achieve a better quality and product performance. Then, in publications [18][19][20] it was presented the mathematical models of dynamic recrystallization (DRX) and steel grain growth 38MnVS6 hot compression tests. Also, the tests of isothermal annealing on the Gleeble-1500 thermomechanical simulator were made.…”
Section: Introductionmentioning
confidence: 99%